Filsafat Idealisme Dan Implementasinya Dalam Pendidikan Islam - Anisatul Mufidah; M. Sugeng Sholehuddin (CV Edujavare Publishing, 2023)
Idealism as a school of philosophy originates from Plato, has had a great influence in all fields of science, including the study of educational philosophy. The philosophy of idealism in principle emphasizes the importance of the superiority of the mind, spirit, spirit or ideas over material or material things using metaphysics, epistemology and axiology points of view. This research aims to determine the implementation of the philosophy of idealism in Islamic education. The method used in this research is library research with a qualitative approach. This literature review is a study in the form of books, articles, references related to educational ideals which can be used as references in carrying out similar research, and is also carried out to obtain valid and accurate conclusions. Educational practice according to the philosophy of idealism is reflected in the formulation of concepts regarding objectives, curriculum, methods, students and teachers (educators).